1956
DOI: 10.1128/jb.72.1.34-41.1956
|View full text |Cite
|
Sign up to set email alerts
|

SPORULATION REQUIREMENTS OF BACILLUS COAGULANS VAR. THERMOACIDURANS IN COMPLEX MEDIA

Abstract: A survey of several strains of Bacillus coagulans var. thermoacidurans revealed considerable variation in sporulation when the organisms were cultured on a variety of peptone containing media. Our culture of strain 43P was especially lacking in sporulation ability, although it sporulated when cultured on a medium such as tomato juice agar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Spore crops of B. coagulans were grown as surface cultures in Roux bottles on the proteose peptone acid agar of Frank (1955) supplemented with 10 ug per ml of MnSO4 H20 (Amaha et al, 1956). After incubation for 2 weeks at 55 C the spores were harvested as described by Frank (1955) and washed 5 times with sterile 0.01 M potassium phosphate buffer, pH 7.2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Spore crops of B. coagulans were grown as surface cultures in Roux bottles on the proteose peptone acid agar of Frank (1955) supplemented with 10 ug per ml of MnSO4 H20 (Amaha et al, 1956). After incubation for 2 weeks at 55 C the spores were harvested as described by Frank (1955) and washed 5 times with sterile 0.01 M potassium phosphate buffer, pH 7.2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…2). Bacillus cereus spores were prepared according to the method of Amaha et al (1). The spore suspension was used after incubation at 65ЊC for 45 min.…”
mentioning
confidence: 99%
“…kills the organisms and thus prevents sporulation. Amaha, Ordal, and Touba (1956) have shown in shake culture that sporulation will occur in 5 days if placed in 10 % tomato serum at 45 C. In their study, the percentage of sporulation varied from 10 to 98 c, varying with the particular strain. These workers also showed the importance of MnSO4 on sporulation of strains of B. coagulans.…”
mentioning
confidence: 94%
“…Pederson and Becker (1949), Becker and Pederson (1950), and Rice and Pederson (1954) found that the pH of the juice is the main factor influencing the growth of B. coagulans. Amaha et al (1956) have shown that tomato juice serum with an initial pH of 7 is a satisfactory medium for sporulation. The main problem appears to be obtaining a pH which supports vegetative growth long enough to allow sporulation to occur.…”
mentioning
confidence: 99%